2017
DOI: 10.18632/oncotarget.21866
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of [99mTc]Tc-Sestamibi in the assessment of thyroid nodules

Abstract: [99mTc]Tc-Sestamibi (MIBI) is an increasingly used tool for evaluation of thyroid nodules. However, there is a lack of evidence about the accuracy of this method in the European population. The aim of this study was to assess the utility of MIBI for the differentiation of thyroid nodules in a large cohort. 161 patients underwent MIBI, followed by a thyroidectomy. We used a dual phase MIBI protocol. Interpretation of the images included a scoring system from 0 (absent) to 3 (increased); this was to provide a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Метаанализ 21 исследования 2013 г. показал чувствительность 82% и специфичность 46% для различения злокачественных и доброкачественных узлов, показатели несколько выше, если взять в анализ только «холодные» узлы (82% и 63% соответственно) [53]. Однако многие авторы отмечают высокое негативное предиктивное значение, достигавшее в некоторых исследованиях >97% [54], что делает 99m Tc-МИБИ ценным именно для исключения злокачественного потенциала узла. Кроме того, ряд модификаций метода может также увеличить его диагностическую точность.…”
Section: радионуклидная диагностикаunclassified
“…Метаанализ 21 исследования 2013 г. показал чувствительность 82% и специфичность 46% для различения злокачественных и доброкачественных узлов, показатели несколько выше, если взять в анализ только «холодные» узлы (82% и 63% соответственно) [53]. Однако многие авторы отмечают высокое негативное предиктивное значение, достигавшее в некоторых исследованиях >97% [54], что делает 99m Tc-МИБИ ценным именно для исключения злокачественного потенциала узла. Кроме того, ряд модификаций метода может также увеличить его диагностическую точность.…”
Section: радионуклидная диагностикаunclassified
“…Moreover, FNAC can be challenging in patients with multinodular goiter or nodules in an unfavorable location (i.e. below the thoracic aperture), and should not be performed on patients on anticoagulant therapy [6]. Molecular imaging with 99m Tc-methoxy-isobutyl-isonitrile ( 99m Tc-MIBI, MIBI) has been used in the assessment of TNs for more than two decades [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that a MIBI negative TN has a high probability of being a benign lesion [10,[13][14][15], thus, making MIBI imaging a suitable tool to ruleout malignancy. On the other hand, relatively low specificity and accuracy have been described [6][7][8]. Selecting hypofunctioning nodules for MIBI imaging increases the overall accuracy, as hyperfunctioning nodules are commonly benign but MIBI positive due to an increased vascularization and higher proliferation rate of hyperfunctioning follicular cells.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas autonomous TN are considered to be benign, larger hypofunctioning nodules require additional diagnostic procedures to rule out a malignant nodule [2,5,21]. However, the role of FNAB is limited in multinodular goiter as well as in lesions that are difficult to access [19,24]. Moreover, up to 40 % of FNAB are non-diagnostic or reveal indeterminate results, with the consequence of diagnostic thyroid surgery in a relevant number of patients [3,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…A MIBI negative TN has a low risk of malignancy with a negative predictive value of MIBI scintigraphy exceeding 90 %. However, the available studies show a broad range of values for the specificity of 15 % to 95 % and 16 % to 100 % for the positive predictive value of MIBI scintigraphy, depending on the prevalence of malignant nodules and the mode of image interpretation, e. g. visual or semi-quantitatively [2,5,12,14,16,17,19,20,23,24]. For the image interpretation of MIBI scintigraphy, the MIBI uptake of hypofunctioning TN is compared to the MIBI uptake of the paranodular tissue.…”
Section: Introductionmentioning
confidence: 99%